2022
DOI: 10.3389/fphys.2022.809363
|View full text |Cite
|
Sign up to set email alerts
|

12 Weeks of Physical Exercise Attenuates Oxidative Stress, Improves Functional Tests Performance, and Reduces Fall Risk in Elderly Women Independently on Serum 25(OH)D Concentration

Abstract: The study aimed to evaluate if the 25(OH)D concentration is related to physical training responses. Moreover, to determine the association between serum 25(OH)D concentration and older women’s physical performance, oxidative stress markers, inflammation, and bone metabolism. 37 older women (age 72.9 ± 5.2 years) were assigned into two groups: supplemented (SG) and non-supplemented (NSG). Then, the participants from SG and NSG were randomly assigned into exercised and non-exercised groups: exercise sufficient v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…A study published in 2016 found that, for hypertensive elderly women, a strength training program could reduce oxidative stress and correlate moderately with cardiovascular benefits ( Dantas et al, 2016 ). And a study published in 2022 by Rodziewicz-Flis’ team demonstrated that a 12-week training contained low-intensity resistance exercise improved physical performance and antioxidant protection in elderly women ( Rodziewicz-Flis et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2016 found that, for hypertensive elderly women, a strength training program could reduce oxidative stress and correlate moderately with cardiovascular benefits ( Dantas et al, 2016 ). And a study published in 2022 by Rodziewicz-Flis’ team demonstrated that a 12-week training contained low-intensity resistance exercise improved physical performance and antioxidant protection in elderly women ( Rodziewicz-Flis et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…All studies were performed exclusively on women, with mean ages ranging from 24•75 to 80•35 years. The studies were conducted between 1995 and 2022 in South Korea (9,(20)(21)(22) , Poland (23) , China (24)(25)(26) , Denmark (27,28) , Japan (29)(30)(31)(32)(33)(34)(35)(36)(37) , Brazil (38) , Finland (10) , Spain (11,39) , UK (40,41) , USA (42) , New Zealand (43) , Greece (44) , Australia (45,46) , Germany (47) and the Netherlands (48) . The dosage of vitamin D supplementation/fortification varied from 10 μg/d to 200 000 μg/3 months, and the intervention period ranged from 4 to 96 weeks.…”
Section: Study Characteristics For Randomised Controlled Trialsmentioning
confidence: 99%
“…The dosage of vitamin D supplementation/fortification varied from 10 μg/d to 200 000 μg/3 months, and the intervention period ranged from 4 to 96 weeks. All studies had a parallel randomised design and were conducted on postmenopausal women with osteopenia/ osteoporosis (9,(20)(21)(22)24,(29)(30)(31)(32)(33)(34)36,39) , healthy postmenopausal women (10,23,25,26,28,35,37,38,(40)(41)(42)(44)(45)(46)(47)(48) and healthy women aged 18-49 years (11,27,43) . Of the thirty-two included studies, fifteen provided data on sCTX (9,10,20,21,(24)(25)(26)(27)(28)(38)(39)(40)(42)(43)(44) and four reported uNTX (11,…”
Section: Study Characteristics For Randomised Controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased daily activities or physical exercises improve the appetite, which may reduce the risk of sarcopenia (60,61). Moreover, exercises can trigger gut microbiota secreting short-chain fatty acids with anti-inflammatory effects, reduce oxidative stress, and maintain muscle mass (62)(63)(64). Older adults having pro-inflammatory diets may potentiate the incident risk of sarcopenia (65).…”
Section: 184mentioning
confidence: 99%